The development and validation of an instrument for labour epidural analgesia recordkeeping in hospitals in Southern Gauteng - Jacobs, Elizabeth Johanna (My University, 2015)
Adverse events are a potential outcome, no matter how skilled the anaesthetist, or how stringently he/she observes protocol. The medical notes made after regional procedures are poor in comparison with those made for general anaesthesia, and this has come under scrutiny in recent years due to increased patient awareness, medical insurance billing strategies and the presence of regulatory bodies. Currently, different labour epidural anaesthesia records are used in the hospitals affiliated to the Department of Anaesthesiology at the University of the Witwatersrand. There is a need for standardised labour epidural anaesthesia records that comply with the minimum standards of the Health Professions Council of South Africa. The aim of this study was to develop and validate an instrument for labour epidural analgesia recordkeeping, using local and national experts and following the two stages of instrument validation described by Lynn. In the development stage, the concept instrument, identifying items considered important on anaesthetic records, was developed through literature review. The concept instrument was refined by a peer group discussion with local experts and the items rated with a four point Likert scale. Items were added, removed or changed according to their ratings. The concept instrument became known as the rated instrument and the items on it were again rated with a four point Likert scale, this time by a national expert panel, and items changed or removed according to Content Validity Indices. The results showed that most of the clinical aspects which are deemed important for labour epidural analgesia recordkeeping by the international anaesthetic community also apply to South Africa. The page layout and presentation of the labour epidural chart is not considered important in a South African context. The information gained from using this instrument in a clinical context can be incorporated into a usable format to facilitate labour epidural analgesia recordkeeping.
A research report submitted to the Faculty of Health Sciences, University of the Witwatersrand, Johannesburg, in partial fulfilment of the requirements for the degree of Master of Medicine in Anaesthesiology. Johannesburg, 2015